2003
DOI: 10.1210/er.2002-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between the Glucocorticoid Receptor and Nuclear Factor-κB or Activator Protein-1: Molecular Mechanisms for Gene Repression

Abstract: The inflammatory response is a highly regulated physiological process that is critically important for homeostasis. A precise physiological control of inflammation allows a timely reaction to invading pathogens or to other insults without causing overreaction liable to damage the host. The cellular signaling pathways identified as important regulators of inflammation are the signal transduction cascades mediated by the nuclear factor-kappaB and the activator protein-1, which can both be modulated by glucocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
616
3
21

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 809 publications
(652 citation statements)
references
References 709 publications
12
616
3
21
Order By: Relevance
“…However, the multivariate analysis did not add any extra information. The cortisol signaling cascade is complex and involves numerous chaperones, accessory proteins, co-regulators and interacting transcription factors that permit differentiation between the MR-and GR-mediated actions (De Bosscher et al, 2003;Pascual-Le Tallec and Lombes, 2005). For instance, recently it was found that increase in recurrence of depressive episodes is associated with a variant in a gene (FKBP5) that regulates GR activity (Binder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the multivariate analysis did not add any extra information. The cortisol signaling cascade is complex and involves numerous chaperones, accessory proteins, co-regulators and interacting transcription factors that permit differentiation between the MR-and GR-mediated actions (De Bosscher et al, 2003;Pascual-Le Tallec and Lombes, 2005). For instance, recently it was found that increase in recurrence of depressive episodes is associated with a variant in a gene (FKBP5) that regulates GR activity (Binder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor AP-1 mediates gene regulation in response to a broad range of physiological and pathological stimuli, including cytokines, growth factors, ROS, infection and other stress signals as well as oncogenic stimuli [353,385,[389][390][391][392][393][394]. In addition, steroid producing tissues are thought to require AP-1 for the regulation of steroidogenesis [387,[385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400].…”
Section: Ap-1 Transcription Factormentioning
confidence: 99%
“…In addition, steroid producing tissues are thought to require AP-1 for the regulation of steroidogenesis [387,[385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400]. AP-1 transcription factors are homo-and hetero-dimers of Jun (c-Jun, JunB and JunD), Fos (c-Fos, FosB, FosB splice variants FosB2 and DeltaFosB2 and Fra-1 and Fra-2) Jun dimerization partner (JDP1 and JDP2) and the closely related activating transcription factor (ATFa, ATF2, LRF1/ATF3, B-ATF) family of proteins characterized by basic region and leucine-zipper domains [353,385,[389][390][391][392][393][394]. In addition, some of the Maf proteins (vMaf, c-Maf and Nrl) can heterodimerize with c-Junior c-Fos, whereas other Maf related proteins, including MafB, MafF, MafG and MafK, heterodimerize with c-Fos but not with cJun.…”
Section: Ap-1 Transcription Factormentioning
confidence: 99%
See 1 more Smart Citation
“…26 Therefore, the treatment of Graves' ophthalmopathy with glucocorticoids is predominantly directed against the NF-kB signaling pathway. 27,28 To analyze further the effect of NFKB1 vs other environmental and demographic factors on the development of eye symptoms, we applied multiple logistic regression analysis. In both cohorts the NFKB1 polymorphism increased the risk of developing eye disease.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 99%